Standards of Practice in Postsecondary Special Needs Programming: Student and Administrator Opinion - Reed, M. J.; Lund-Lucas, E.; O’Rourke, K. (Canadian Journal of Higher Education, 2003)
Standards of practice for postsecondary special needs programmes are an important element to determining programme effectiveness and programme successes. A number of groups have now suggested practice standards for postsecondary special needs programmes. We amalgamated these suggested practices and queried Ontario students and administrators regarding their opinion of these practice standards. Overall, strong support for most suggested practices was found among students and administrators. However, administrators less strongly supported practices that required enhanced funding, staffing and resources. In addition, students less strongly supported practices that could reduce individualized programming and increase time commitments. Administrators pointed out barriers to achieving practice standards. Time commitments, workload, funding, unclear working definitions (i.e., standards for transition, disabilities) and institutional policy constraints were barriers to achieving suggested practice standards.